Interfaculty collaboration for improving international mobility experiences: sustaining a dialogue across difference. Issue 1 (2nd January 2023) - Fitzgerald, Ange; Parr, Graham; Williams, Judy; Wellam, Rachel; Howard, Bethany; Zandes, Stavroula; Diug, Basia
ABSTRACT: Higher education institutions promote interfaculty collaborations in research and education projects, but few studies have examined the challenges of such collaborations. This case study investigates how a heterogeneous interfaculty group worked in a community of practice for two years curating an educational e-resource to support the professional learning of academic leaders of student international mobility experiences in their university. Focusing on the journey of working within this community of practice rather than the destination (the e-resource they produced), the study explores how the different members of the group negotiated the tensions and uncertainty associated with an interdisciplinary collaboration. Data in the form of reflexive 'critical incident' narratives written by all seven authors reveal the challenges of sustaining a 'dialogue across difference' in this cross-disciplinary collaboration. The study supports existing research that argues interfaculty collaborations are potentially rich and generative, but shows why success should not be taken for granted.